Association of peripheral NK cell counts with Helios+IFN-γ– Tregs in patients with good long-term renal allograft function. (13th March 2017) - Trojan, K; Zhu, L; Aly, M; Weimer, R; Bulut, N; Morath, C; Opelz, G; Daniel, V
Summary: Little is known about a possible interaction of natural killer (NK) cells with regulatory T cells (Treg ) in long-term stable kidney transplant recipients. Absolute counts of lymphocyte and Treg subsets were studied in whole blood samples of 136 long-term stable renal transplant recipients and 52 healthy controls using eight-colour fluorescence flow cytometry. Patients were 1946 ± 2201 days (153–10 268 days) post-transplant and showed a serum creatinine of 1·7 ± 0·7 mg/dl. Renal transplant recipients investigated > 1·5 years post-transplant showed higher total NK cell counts than recipients studied < 1·5 years after transplantation ( P = 0·006). High NK cells were associated with high glomerular filtration rate ( P = 0·002) and low serum creatinine ( P = 0·005). Interestingly, high NK cells were associated with high CD4 + CD25 + CD127 – forkhead box protein 3 (FoxP3 + ) Treg that co-express the phenotype Helios + interferon (IFN)-γ – and appear to have stable FoxP3 expression and originate from the thymus. Furthermore, high total NK cells were associated with Treg that co-express the phenotypes interleukin (IL)−10 – transforming growth factor (TGF)-β + ( P = 0·013), CD183 + CD62L – ( P = 0·003), CD183 + CD62 + ( P = 0·001), CD183 – CD62L + ( P = 0·002), CD252 – CD152 + ( P < 0·001), CD28 + human leucocyte antigen D-related (HLA-DR – ) ( P = 0·002), CD28 + HLA-DR + ( P < 0·001), CD95 + CD178 – ( P < 0·001) and CD279 – CD152 + ( P < 0·001), suggesting that these activated Treg home in peripheral tissues and suppress effector cells via TGF-β and cytotoxic T lymphocyte-associated protein 4 (CTLA-4). The higher numbers of NK and Treg cell counts in patients with long-term good allograft function and the statistical association of these two lymphocyte subsets with each other suggest a direct or indirect (via DC) interaction of these cell subpopulations that contributes to good long-term allograft acceptance. Moreover, we speculate that regulatory NK cells are formed late post-transplant that are able to inhibit graft-reactive effector cells. Graphical Abstract: